Analysis of Factors Affecting Underpricing in Initial Public Offerings - Anes Liliani Daeli; Ronni Andri Wijaya (UPI YPTK Journal of Business and Economics, 2020)
This research was conducted on companies that made initial public offerings on the Indonesia Stock Exchange in 2013-2017 with the aim of knowing how much influence the level of underwriter reputation, return on assets, company size and earnings per share had on the level of underpricing by using the debt to equity ratio as a moderating variable. . In this study using several analytical techniques including: descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results obtained based on the Partial Test (t) obtained: There is a significant influence between underwriter reputation and return on assets on the level of underpricing. There is no significant effect between firm size and firm size on the level of underpricing. Debt to equity ratio cannot moderate the relationship between underwriter reputation, return on assets, firm size and earnings per share to the level of underpricing. Then based on the results of the Simultaneous Test (Test F) it can be seen that the underwriter's reputation, return on assets, company size and earnings per share have a significant and significant effect on the level of underpricing.